Can the modernisation of a public employment service be an effective labour market intervention? The Hungarian experience, 2004-2008 - Zsombor Cseres-Gergely (European Journal of Government and Economics (EJGE), 2012)
The Public Employment Service often delivers much of the employment policy including active labour market programmes in many member states in the EU, yet we know little about its effectiveness in general. This paper provides a quantitative assessment of the potential impact of the modernisation programme of the Hungarian Public Employment service between 2004 and 2008. Using data at the level of local offices, I calculate programme effects using a difference-in-difference estimator. Results show that the programme has increased re-employment rates significantly, by 6%. The modernisation was thus a moderately effective but relatively inexpensive intervention, similar in terms of cost-effectiveness to the better active labour market programmes in Hungary.
Keywords: 330; older workers; youth employment; labour demand; public sector